Speleonymia Slovenského rudohoria z pohľadu teórie modelovania - Rožai, Gabriel (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article presents model analysis of non-standardized names of caves and chasms of the Slovenské rudohorie mountains which follows the model analysis of anoikonyms by Jana Pleskalová, as well as the work devoted to modelling of Slovak hydronymy. The model analysis pointed out the dominance of the relational model C which expresses “properties, symptoms (and circumstances)” and the relational model A which is associated with the expression of “position, the location of underground object in the field”. The most common structural model in the given relational models is the two-member ADd+S, consisting of a derivative adjective and a noun such as Jelšavská jaskyňa, Gajdova štôlňa. Relational models (VM) referring to possessivity (VM D), especially to the immediate expression of the type of object (VM B), only have a marginal position in the proposed model analysis.